Exploring Ecojustice & Environmental Learning through Online Preservice Teacher Education - Sperling, Erin; Inwood, Hilary; Sims, Laura; Elliott, Paul (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
As teacher education can help communities transition to sustainable, just ways of being, this study reports on the development of, and research on, a national E-course for preservice teachers focused on Environmental and Sustainability Education (ESE). This collaborative initiative brought together academics, community educators, and K-12 teachers to offer participatory, locally-relevant online ESE learning. By facilitating learning centred on concepts of indigenization, ecojustice, and place-based learning, the E-course aimed to ensure equitable access to ESE for preservice teachers across Canada. We ask, what are participants’ experiences and the impact of their involvement in this E-course? Using a socio-critical lens, the authors draw on survey data to report on the outcomes of the E-course. We hope that it may serve as a new model for online ESE for preservice teacher education, and more broadly highlight the capacity for building understanding about ecojustice education and community connections through virtual learning spaces.